Analisis Perkembangan Kemampuan Mengidentifikasi Variabel pada Mahasiswa Pendidikan Kimia Tingkat Awal (HISKIA : Jurnal Ilmu Kimia & Pendidikan Kimia, 2025)
Abstract. This study analyzed the development of variable identification skills among early-level chemistry education students, a crucial component of scientific literacy and experimental design. The research addressed the varied initial competencies and the progression of these skills over time, identifying common difficulties. Employing a quantitative descriptive-longitudinal design, the study involved 8 chemistry education students from a university in Indonesia. Data were collected through written tests at three time points (beginning, middle, and end of the semester) to measure the ability to identify independent, dependent, and control variables. Supplementary qualitative data from observations and interviews provided deeper insights into student difficulties and contributing factors. Results indicated a significant improvement in students' variable identification skills throughout the semester, with average scores increasing from 65.0 to 79.8. Despite overall progress, students consistently faced challenges, particularly in distinguishing between independent and control variables and identifying implicitly stated dependent variables. Factors contributing to this development included prior practical experience, explicit instruction from lecturers, and active group discussions. The findings highlight the importance of structured learning experiences and targeted interventions to address specific misconceptions in developing fundamental scientific process skills among prospective chemistry teachers.